1991
DOI: 10.1093/rheumatology/30.2.125
|View full text |Cite
|
Sign up to set email alerts
|

Is Diet Important in Rheumatoid Arthritis?

Abstract: There is evidence from several well documented case reports that occasional patients with rheumatoid arthritis (RA) may develop aggravation of their arthritis as a result of allergy to some ingredient in the diet. A variety of foodstuffs have been implicated including milk and milk products, corn and cereals. Total fasting results in improvement in rheumatoid arthritis, but appears to be mediated by diminution in production of chemical mediators of inflammation, rather than by elimination of a dietary allergen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1993
1993
2001
2001

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Im provement of the nutritional state of the pa tient is also crucial. In rheumatological disor ders, the role of nutritional treatment is not established [33], In our study oral bacteriotherapy with Lac tobacillus GG appeared to act as an immunotherapeutic agent promoting the antigen-spe cific IgA immune response, specifically in Crohn's disease and irrespective of its activity possibly indicating an intrinsic defect in the Ann NulrMclab 1996;40:137-145immunological barrier of the gut. We suggest that the oral bacteriotherapy balanced that barrier.…”
Section: Discussionmentioning
confidence: 52%
“…Im provement of the nutritional state of the pa tient is also crucial. In rheumatological disor ders, the role of nutritional treatment is not established [33], In our study oral bacteriotherapy with Lac tobacillus GG appeared to act as an immunotherapeutic agent promoting the antigen-spe cific IgA immune response, specifically in Crohn's disease and irrespective of its activity possibly indicating an intrinsic defect in the Ann NulrMclab 1996;40:137-145immunological barrier of the gut. We suggest that the oral bacteriotherapy balanced that barrier.…”
Section: Discussionmentioning
confidence: 52%
“…The control of RA by dietary manipulation has been infrequently tested and has not always yielded convincing results (Shatin, 1964;Ziff, 1983;Darlington et al 1986;Buchanan et al 1991), probably because the gastrointestinal tract may not play a pathogenic role in all cases of RA and because most previous clinical trials have only controlled for single, rather than multiple dietary elements which may simultaneously influence disease expression and progression. Van de Laar & van der Korst (1992) demonstrated symptomatic improvement in a subset of patients with RA who were seropositive for RF when they were placed on elemental diets (protein-free diets consisting of essential amino acids, glucose, trace elements and vitamins).…”
Section: Clinical and Experimental Evidence Implicating Diet In Rheummentioning
confidence: 99%
“…Other investigators were unable to reduce clinical complaints through avoidance diet in rheumatoid arthritis (72, 73). However, Panush et al analyzing anecdotal cases, suggested that immune reactions provoked by foods may lead to tissue injury and abnormal immune reactions in the joints, and thus conditions known as “rheumatic diseases” may develop ( 74).…”
Section: Diseases Presumed To Be Caused By Adverse Reactions To Foodmentioning
confidence: 99%